Hand-assisted laparoscopic surgery for colon and rectal resection: a single-institution experience in 473 patients - Kuliešius, Žygimantas; Dulskas, Audrius; Kuliavas, Justas; Rudinskaitė, Giedrė; Samalavičius, Narimantas E. (Lietuvos chirurgija, 2017)
Background / Objective Hand-assisted laparoscopic surgery (HALS) has been introduced into clinical practice for almost three decades. It combines the advantages of both laparoscopic (minimally invasive) and conventional open surgery. Despite all the published data, there are still scepticism in surgical community regarding this hybrid form of laparoscopic surgery and the role of HALS is still being defined. Our study aimed to review 10 year experience in treating patients at single centre with colonic and rectal pathology using HALS.Methods This study was a retrospective analysis of prospectively collected data of 473 patients undergoing hand assisted laparoscopic colorectal surgery for colon and rectal disease, mainly cancer, in a single tertiary care institution, National Cancer Institute, from January, 2006, to July, 2016. All consented patient with colonic and rectal pathology were included in the analysis. Results The patients’ mean age was 64.14 ± 9.75 years. Female and male ratio was similar 240 (50.73%) vs. 233 (49.27%). The mean length of postoperative hospital stay was 6.92, ranging from 2 to 34 days. Histological examination revealed mean lymph node harvest was 16.97 ± 12.10. Stage I, II, III cancer groups were similar accounting for 142 (30.02%), 139 (29.35%) and 153 (32.35%) cases respectively, stage IV – 36 (7.61%) and three cases of benign origin. Segmental colectomies were performed in 53.0% cases, 45.3% patients had rectal resections and “other” 1.7%. Surgical re-intervention was required for 10 patients (2.11%). Complication rate was 6.55%, and mortality documented in only 2 cases (0.42%).Conclusion HALS is safe and feasible technique, which maintains all the benefits of laparoscopic colectomy and can be performed for numerous indications, while affording the surgeon to carry out complex cases in a minimally invasive fashion.
Keywords: laparoscopic colectomy; hand-assisted laparoscopy; colon cancer